Induced EEG activity during the IAPS tests and avEMT in intimate partner violence against women (2018)
Intimate Partner Violence (IPV) against women is a major problem in Colombia. Nowadays the question about the effects of violence on women and the identification of latent risks that affect their health, is increasingly relevant. This article describes a pilot study that aimed to measure electrophysiological signals corresponding to the emotional neurophysiological response of women who had experienced IPV in contrast to those who did not. Six healthy female adults, ranged in age from 18 to 55 years old enrolled in this study. For the measurement we used the International Affective Picture System (IAPS) and an Auditory and Visual Emotional Memory Test (avEMT), and we recorded the EEG signal with a g.Nautilus 32 g.LadyBird. EEG signals acquired from baseline and during the tests were compared. As a result of IAPS test, we found for all the participants a higher power spectrum at low EEG frequencies and a decrease in power as the frequencies increase for baseline and emotional pictures. For the avMET, both groups show a higher power spectrum in the different phases of the task compared with the baseline, with an exception of one participant from the WIPV group who show the opposite tendency. Also, two machine learning models were trained and an accuracy of more than 85% were achieved to classify EEG signals from women who experienced IPV and women who had not. This research is an approach to the phenomenon of violence against women and broadens the understanding of the effects on emotional response and electrophysiological activation in women who have experienced this type of situation.